Didymoplexis gibbosa (Orchidaceae), a new mycoheterotrophic species from southern Vietnam - Averyanov, Leonid V.; Maisak, Tatiana V.; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nuraliev, Maxim S. (Phytotaxa, 2022)
The paper presents a description of a new species, Didymoplexis gibbosa (Gastrodiinae, Gastrodieae) discovered recently in southern Vietnam. This is the fifth species of the genus reported from Vietnam. The new species is most similar to the widely distributed D. pallens. Description of the discovered species is accompanied with data on ecology, phenology and distribution, estimated IUCN Red List status, studied specimens, brief taxonomic notes and illustrations.